Mycological quality of pecan nuts from Brazil: absence of aflatoxigenic fungi and aflatoxins - Garcia,Marcelo Valle (2019)
ABSTRACT: In recent years, Brazil has encouraged the cultivation of pecans to meet both demands of domestic and international market of nuts. New genetic varieties of pecans have been selected in recent years, but available scientific information on the occurrence of fungi and aflatoxins in the international literature is out of date. Therefore, the present study aimed to quantify and identify fungal microbiota and the presence of aflatoxins in pecan nuts cultivated in southern Brazil. Fifty-two pecan nut lots (Barton variety) were obtained from producers from 19 cities of Rio Grande do Sul State and analyzed by direct plating in Agar Dichloran Glycerol 18% (DG18) and Aspergillus Flavus and Parasiticus Agar (AFPA), following incubation at 25 °C for 7 days. Aflatoxins analyses were carried out using HPLC coupled with a mass spectrometer. Results revealed at least 10 different genera of fungi. Aspergillus, Penicillium, Fusarium, and Cladosporium were predominant. Xerophilic species of Aspergillus (A. wentii, A. ruber, A. pseudoglaucus, and A. chevalieri) were commonly reported in the samples. No potential aflatoxin-producing species was isolated and no aflatoxins were detected (LOQ=1 μg/kg and LOD=0.1 μg/kg for AFB1 and AFB2, and 0.3 μg/kg for AFG1 and AFG2) in the evaluated samples. The absence of this carcinogenic group of mycotoxins is highly positive and could boost the investments in the sector, as well as stimulate the commercialization and consumption of this variety of nut.